Transnational Protest, Australia and the 1960s - Piccini, Jon. author. aut Link
XVI, 251 p.
Keywords: Australia is rarely considered to have been a part of the great political changes that swept the world in the 1960s: the struggles of the American civil rights movement, student revolts in Europe, guerrilla struggles across the Third World and demands for women’s and gay liberation. This book tells the story of how Australian activists from a diversity of movements read about, borrowed from, physically encountered and critiqued overseas manifestations of these rebellions, as well as locating the impact of radical visitors to the nation. It situates Australian protest and reform movements within a properly global – and particularly Asian – context, where Australian protestors sought answers, utopias and allies. Dramatically broadens our understanding of Australian protest movements, this book presents them not only as manifestations of local issues and causes but as fundamentally tied to ideas, developments and personalities overseas, particularly to socialist states and struggles in near neighbours like Vietnam, Malaysia and China.'Jon Piccini is Research and Teaching Fellow at The University of Queensland, Brisbane, Australia. His research interests include the history of human rights and social histories of international student migration.'.